Electrochemical characterization of the interaction between ammonium nitrate and reactive ground. (20th December 2019) - Conroy, Gregory; Robinson, Kelly; Beach, Fiona; Donne, Scott W.
Abstract: Cyclic voltammetry is used to examine the interaction between aqueous solutions of NH4 NO3 and FeS2, a major component of reactive ground. Voltammetric processes corresponding to the Fe(II)/Fe(III) redox couple and the reduction of nitrate are observed. This is significant as the existing reaction mechanism shows nitrate reacting in the electrolyte, but not being reduced on the surface of the FeS2 . An irreversible oxidation occurs at ∼0 V versus SCE associated with the re-oxidation of species formed at lower potentials. This is not associated with a change in the potential of the electrolyte, indicating a surface reaction. With the use of thermocouples, an exothermic reaction above 0.4 V is observed. FeS2 is initially unreactive in NH4 NO3 solutions. After FeS2 exposure to potentials above 0.6 V versus SCE, the material becomes active and catalytic in nature. Material reacted following the industry standard Australian Explosives Industry Safety Group (AEISG) test method shows similar catalytic behaviour in the presence of fresh NH4 NO3 . This is significant for the safety and testing of reactive ground, as even FeS2 that has completed reaction still has the potential to undergo further reaction if introduced to fresh NH4 NO3 . Highlights: Electrochemistry may be used to investigate reactive ground processes. Commercially obtained FeS2 may be used to study reactive ground chemistry, reducing reliance on variable ground samples. FeS2 can be shown to go from an inert to a catalytic state with the application of high potentials in ammonium nitrate.